Neurodevelopmental outcome at early school age of children born to mothers with gestational diabetes. Issue 1 (1st July 1999) - Ornoy, A; Wolf, A; Ratzon, N; Greenbaum, C; Dulitzky, M
Abstract : AIMS: To study the metabolic derangements in the second half of pregnancy caused by gestational diabetes, on the long term development of children. METHODS: The neuropsychological function of 32 school age children born to 32 mothers with well controlled gestational diabetes and 57 control children matched by age, birth order, and parental socioeconomic status was studied. RESULTS: There were no differences in head circumference and height, but the children born to diabetic mothers were heavier. The verbal IQ scores of index children below the age of 9 years were lower than those of control children. No differences were found between the groups in various sensory and motor functions and in the Touwen and Prechtl neurological test. The young index group children performed less well than controls in fine and gross motor functions, as observed on the Bruininks–Oseretzky test of motor proficiency. The scores of young children born to mothers with gestational diabetes were also lower than controls on the Pollack tapper test, and there were more index group children who scored abnormally on the parents' Conners questionnaire . No correlation was found between the performance of the index group children on various neurodevelopmental tests and the severity of perinatal complications. The differences tended to disappear with age. CONCLUSIONS: Gestational diabetes, as a result of the metabolic abnormalities in the second half of pregnancy, induces long term minor neurological deficits which are more pronounced in younger children. There does not seem to be any direct relation between the appearance of congenital anomalies and neurodevelopmental outcome.